Middle Segment-Preserving Pancreatectomy for Recurrent Metastasis of Renal Cell Carcinoma after Pancreatoduodenectomy: A Case Report - Aiyama Takeshi; Inagaki Mitsuhiro; Akabane Hiromitsu; Yanagida Naoyuki; Shibaki Taiichiro; Shomura Hiroki; Kudo Takeaki; Shonaka Tatsuya; Oikawa Futoshi; Sakurai Hiroharu; Nakano Shiro (Case Reports in Surgery)
Many cases of surgical resection of metastatic pancreatic tumors originating from renal cell carcinoma have been reported; however, cases of reresection of recurrent pancreatic metastasis of renal cell carcinoma in the remnant pancreas are rare. We performed a second resection for recurrent pancreatic metastasis of renal cell carcinoma six years after pancreatoduodenectomy with pancreaticogastrostomy reconstruction. By performing middle segment-preserving pancreatectomy, we were able to successfully spare the exocrine and endocrine pancreatic function compared to that observed after total pancreatectomy, with no signs of recurrence for two years after the surgery.